A prova ilícita no Direito Tributário: um estudo sobre a (in)admissibilidade no processo administrativo federal - Costa, Myrella Cristine Trevisan da (2020)
The purpose of this dissertation is to investigate the admissibility or inadmissibility of illicit evidence by the federal tax authorities. We begin examining the issue by highlighting the role of language in knowledge and truth for the law and how the theory of evidence is extremely relevant to the formation of the tax legal fact, in order to emphasize its indispensability for the support of concrete and individual rules by the Public Administration. Based on this, we examine the elements and requirements for valid evidence, taking into account specifically the evidence obtained by illicit means and its consequences in tax law. In order to better elucidate the matter of illicit evidence, we review its historical background and management both in international and national legal systems, notedly in constitutional, criminal and civil spheres. Finally, we analyze the case of illicit evidence in tax law, particularly in the federal administrative sphere, based on precedents given by the Administrative Council for Tax Appeals (CARF)